The Healthy Gluten-Free Diet: Practical Tips to Prevent Metabolic Disorders and Nutritional Deficiencies in Celiac Patients - Emanuele Rinninella; Marco Cintoni; Pauline Raoul; Silvia Triarico; Tommaso Dionisi; Giovanni Battista Gasbarrini; Antonio Gasbarrini; Maria Cristina Mele (Gastroenterology Insights, 2021)
The gluten-free diet (GFD) is the cornerstone treatment for coeliac disease (CD). However, a healthy GFD is more complex than the only exclusion of gluten-containing foods. Most celiac patients do not receive nutritional advice and tend to consume industrial gluten-free products (GFPs), which often lack fiber, vitamins, and other micronutrients while being rich in saturated fats and refined sugars. This review focuses on the main potential metabolic disorders and nutritional deficiencies in CD patients at diagnosis and dissects the main nutritional and metabolic issues due to a non-balanced GFD. Nutritional tips to achieve an adequate dietary approach in CD are provided. We also compared the main nutritional components of naturally gluten-free cereals (including pseudocereals) to give an exhaustive overview of the possible healthy alternatives to processed GFPs. Clinicians and dietitians should be systematically involved in the diagnosis of CD to monitor the appropriateness of GFD and the patient’s nutritional status over time.